ADHD and Problem Behaviour: A Neuropsychological Approach - Lalatović, Staša; Popović Ćitić, Branislava; Krstić, Nadežda; Pavlović, Viktor (Psihološka istraživanja, 2026)
Evidence suggests that Attention-Deficit/Hyperactivity Disorder (ADHD) occurs more frequently among children and adolescents with problem behaviour than in the general population. This has often led to the conclusion that ADHD represents a specific risk factor for the development of various forms of delinquent behaviour. Rather than accepting this assumption uncritically, a more precise understanding of the complex relationship between ADHD and problem behaviour requires an examination of the underlying neurocognitive mechanisms involved in the emergence and functioning of both ADHD and different forms of problem behaviour. This paper places particular emphasis on executive and verbal functions, which have proven especially important in clarifying this association, as well as on the domain of social cognition, whose relevance in this context has received increasing attention. In addition, neurobiological mechanisms that may contribute to the co-occurrence of ADHD and conduct disorder (CD) are discussed. Beyond the conclusion that ADHD in itself constitutes a (limited) risk factor primarily for impulsive, less violent forms of problem behaviour, this paper underscores the importance of neuropsychological monitoring of children and adolescents with behavioral difficulties. Particular attention should be directed toward individuals with CD, given the implications of such monitoring for the further development of therapeutic approaches.
Keywords: ADHD; problem behaviour; conduct disorder; neuropsychology